XALÍQ MIGRACIYASÍNÍŃ QÁLIPLESIWI HÁM ONÍŃ HÁREKETI - Auezov, Ó.T. (SCIENCE and SOCIETY, 2023)
This article examines the migration zones of the cities and districts of the Republic of Karakalpakstan.
Keywords: migration movement; emigration; immigration; remigration; external migration; internal migration